Levels of interleukin-6 in tears before and after excimer laser treatment - Resan, Mirko R; Stanojević, Ivan; Petković Ćurčin, Aleksandra; Pajić, Bojan; Vojvodić, Danilo (Vojnosanitetski pregled, 2015)
Background/Aim. Immune response and consequent inflammatory process which originate on ocular surface after a trauma are mediated by cytokines. Photoablation of corneal stroma performed by excimer laser causes surgically induced trauma. Interleukin-6 (IL-6) is mostly known as a proinflammatory cytokine. However, it also has regenerative and anti-inflammatory effects. It is supposed that this cytokine is likely to play a significant role in the process of corneal wound healing response after photoablation of stroma carried out by laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK) methods. The aim of this study was to determine and compare the levels of IL-6 in tears before and after treatment with LASIK and PRK methods. Methods. The study included 68 shortsighted eyes up to -3.0 diopter sphere, i.e. 198 samples of tears (per three samples taken from each of the eyes), divided into two groups according to the kind of excimer laser intervention performed: the group 1 – eyes treated by LASIK method (n = 31), and the group 2 – eyes treated by the PRK method (n = 37). The samples of tears were taken from each eye at the following time points: before excimer laser treatment (0 h, the control group), 1 h after the treatment (1 h) and 24 h after the treatment (24 h). The patients did not use anti-inflammatory therapy 24 h after the intervention. Tear samples were collected using microsurgical sponge. Level of IL-6 in tear fluid was determined by the flow cytometry method, applying a commercial test kit which allowed cytokine detection from a small sample volume. Results. The values of IL-6 were detectable in 16% of samples before LASIK treatment and in 30% of samples before PRK treatment. One h after the treatment IL-6 was detectable in 29% of samples for the LASIK group and 43% of samples for the PRK group, and 24 h after the treatment it was detectable in 19% of samples for the LASIK group and in 57% of samples for the PRK group. When we analyzed the dynamics of IL-6 production in particular groups, we noticed that both in the LASIK and PRK group the number of samples with increased values of IL-6 after 1 h, and after 24 h, was considerably larger than the number of samples with decreased values of IL-6 after the intervention. Analyzing the dynamics of IL-6 concentration changes in the 1 h samples vs 24 h samples there was a statistically significant increase in the number of samples with IL-6 concentration decline in the LASIK group, while at the same time no considerable changes occurred in the PRK group. Comparing average IL-6 values between the two treatment groups in all tear samples at 0 h, 1 h and 24 h after intervention a significantly higher level in the PRK group 24 h after procedure (p = 0.0031) was detected. Conclusion. IL-6 level in tears increases 1 h and 24 h after LASIK and PRK treatments. This increment is significantly larger 24 h after the treatment with the PRK method than with the LASIK method. Changes of IL-6 production levels in tears after excimer laser treatment indicate that this cytokine takes part in the corneal recovery process after stromal photoablation.